2021
DOI: 10.1186/s12870-021-03342-6
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome revealed the molecular mechanism of Glycyrrhiza inflata root to maintain growth and development, absorb and distribute ions under salt stress

Abstract: Background Soil salinization extensively hampers the growth, yield, and quality of crops worldwide. The most effective strategies to counter this problem are a) development of crop cultivars with high salt tolerance and b) the plantation of salt-tolerant crops. Glycyrrhiza inflata, a traditional Chinese medicinal and primitive plant with salt tolerance and economic value, is among the most promising crops for improving saline-alkali wasteland. However, the underlying molecular mechanisms for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 109 publications
0
9
0
Order By: Relevance
“…Now, a growing stream of research suggests that the WRKY gene family plays important roles in plant development and substance metabolism. Many WRKY proteins have been certified in the plant kingdom, which are mainly related to seed dormancy and germination [ 8 , 9 ], embryogenesis [ 10 , 11 ], trichome development [ 12 , 13 ], pollen development [ 14 , 15 ], root development [ 16 ], modulation of flowering time [ 17 ], leaf senescence [ 18 ], plant nutrient utilization [ 19 ], and biosynthesis of secondary metabolites [ 20 ]. Although they play important roles in these situations, more important are their biological functions and molecular regulatory mechanisms in plant responses to biological and abiotic stresses [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Now, a growing stream of research suggests that the WRKY gene family plays important roles in plant development and substance metabolism. Many WRKY proteins have been certified in the plant kingdom, which are mainly related to seed dormancy and germination [ 8 , 9 ], embryogenesis [ 10 , 11 ], trichome development [ 12 , 13 ], pollen development [ 14 , 15 ], root development [ 16 ], modulation of flowering time [ 17 ], leaf senescence [ 18 ], plant nutrient utilization [ 19 ], and biosynthesis of secondary metabolites [ 20 ]. Although they play important roles in these situations, more important are their biological functions and molecular regulatory mechanisms in plant responses to biological and abiotic stresses [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptome, as a useful tool to investigate molecular mechanism of plants because of high accuracy and sensitivity (Smith et al, 2008; Teshome et al, 2020), which some kinds of crop (such as Triticum aestivum and Glycyrrhiza inflata ) had found the mechanism of plants to respond the salt stress through transcriptome (Nakayama et al, 2022; Xu et al, 2021). There are many ways to find candidate genes through transcriptome data including DEGs, co‐expression modules, and WGCNA (Amrine et al, 2015; Du et al, 2022; Langfelder & Horvath, 2008) while KEGG is a useful database to enriched these genes (Chen et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…When plants were exposed to salt stress, many genes were significantly enriched in DEGs in the plant transcriptome ( Xu et al, 2021 ), which were also found to be associated with oxidation-reduction and hydrogen peroxide catabolic processes in S. caseolaris . Based on the GO enrichment analysis, these genes were involved in various molecular functions, including protein disulfide oxidoreductase activity, monooxygenase activity, and oxidoreductase activity.…”
Section: Discussionmentioning
confidence: 99%